Objective Measures of Physical Distancing in the Hospital During the COVID‐19 Pandemic. Issue 9 (18th August 2021) - Tatineni, Swetha; Orlov, Nicola M; Riehm, Joseph M; Erondu, Amarachi; Mozer, Christine L; Cook, David J; Byron, Maxx; Mordell, Lisa; Dimitrov, Michael; Arora, Vineet M
Abstract : During the COVID‐19 pandemic, hospitals published physical‐distancing guidance and created dedicated respiratory isolation units (RIUs) for patients with COVID‐19. The degree to which such distancing occurred between clinicians and patients is unknown. In this study, heat sensors from an existing hospital hand‐hygiene monitoring system objectively tracked room entries as a proxy for physical distancing in both RIUs and general medicine units before and during the pandemic. The RIUs saw a 60.6% reduction in entries per room per day (from 85.7 to 33.8). General medicine units that cared for patients under investigation for COVID‐19 and other patients experienced a 14.7% reduction in entries per room per day (from 76.9 to 65.1). While gradual extinction was observed in both units as COVID‐19 cases declined, the RIUs had a higher degree of physical distancing. Although the optimal level of physical distancing is unknown, sustaining physical distancing in the hospital may require re‐education and real‐time monitoring.